Specificity in Sociality: Mice and Prairie Voles Exhibit Different Patterns of Peer Affiliation - Beery, Annaliese K.; Christensen, Jennifer D; Lee, Nicole S.; Blandino, Katrina L. (Frontiers in Behavioral Neuroscience, 2018)
Social behavior is often described as a unified concept, but highly social (group-living) species exhibit distinct social structures and may make different social decisions. Prairie voles (Microtus ochrogaster) are socially monogamous rodents that often reside in extended family groups, and exhibit robust preferences for familiar social partners (same- and opposite-sex) during extended choice tests, although short-term preferences are not known. Mice (Mus musculus) are gregarious and colonial, but in brief laboratory tests of social preference they typically prefer social novelty. This preference for novel versus familiar peers may represent a species-specific difference in social decision-making between mice and prairie voles. However, the tests used to measure preferences in each species differ markedly in duration and degree of contact, such that the behaviors cannot be directly compared. We assessed whether social preferences for novelty or familiarity differed between mice and prairie voles of both sexes when assessed with matching protocols: the sociability/social preference test typically used in mice (short, no direct contact), and the partner preference test used in voles (long, direct contact). A subset of voles also underwent a partner preference test using barriers (long, no direct contact). In the short social preference test, behavior did not differ between species. In the longer test, pronounced partner preferences emerged in prairie voles, but mice exhibited no social preferences and rarely huddled. No sex differences were evident on either test. Direct physical contact was required to get partner preferences in huddling time in voles, but preference for the partner chamber was evident with or without contact. Both prairie voles and mice are social, but they exhibit important differences in the specificity and extent of their social behavior. While mice are often used to study social approach and other behaviors, voles are a more suitable species for the study of selective social relationships. Consideration of these differences will be important for studies examining the neural mechanisms supporting different kinds of peer social behavior.